2011
DOI: 10.2340/00015555-1022
|View full text |Cite
|
Sign up to set email alerts
|

Patient Education in Chronic Skin Diseases: A Systematic Review

Abstract: The negative impact of skin disease on quality of life (QoL) has been described in many studies. Patient education as an adjunct to treatment, with the aim of improving QoL and reducing disease severity, is a relatively new technique in dermatology. The objective of this article is to analyse and summarise evidence concerning the effects of patient education on QoL and disease severity in patients with chronic skin diseases. All source material was identified through searches in MEDLINE and Embase. The CONSORT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 43 publications
2
39
0
1
Order By: Relevance
“…Following this intervention, patients reported reduced disease severity. Similar results were found with educational interventions in adults [47].…”
Section: Treatments Of Skin-related Psychosocial Problemssupporting
confidence: 78%
See 1 more Smart Citation
“…Following this intervention, patients reported reduced disease severity. Similar results were found with educational interventions in adults [47].…”
Section: Treatments Of Skin-related Psychosocial Problemssupporting
confidence: 78%
“…A review of randomized controlled trials in patients with chronic skin conditions reveals that in particular interventions involving a multidisciplinary team and several meetings, participants reported an improved quality of life and reduced disease severity [47]. One example is the intervention of Staab et al [48] in which a distinction was made between different age groups, and children with atopic eczema and their parents were provided with a structured psychoeducation, consisting of six sessions which were led by a multidisciplinary team (among others a dermatologist, a psychologist, a nurse and a dietician).…”
Section: Treatments Of Skin-related Psychosocial Problemsmentioning
confidence: 99%
“…The value of adjunctive patient education and support as a means of improving quality of life and reducing disease severity in patients with conditions such as atopic eczema has been shown to be of value in a systematic review . However, more recently, a review of interventions used in randomized controlled trials, aimed at patients with psoriasis, concluded that attempts to improve disease severity and quality of life through the provision of educational information have met with limited success …”
Section: Introductionmentioning
confidence: 99%
“…In dermatology, TPE has been mainly used in atopic dermatitis and psoriasis [12]. In our center, the monitoring of a large cohort of children with ichthyosis revealed a strong sense of exclusion among these families, as well as common misunderstandings about the disease [13].…”
Section: Introductionmentioning
confidence: 99%